Efecto del aceite quemado de motor sobre las propiedades físicas y mecánicas de mezclas asfálticas que contienen RAP (2017)
Use of materials from Reclaimed Asphalt Pavement (RAP) is a worldwide trend in production of asphalt mixtures having properties similar to those obtained with new materials. In this study, changes in the physical and mechanical properties of asphalt mixtures containing RAP and waste engine oil (WEO) as a rejuvenating agent of the aged binder contained in the RAP were analyzed , using and MDC-19 mixture pavement, according INVIAS specifications, 450-13, as a reference. Results obtained suggest that WEO as a rejuvenating agent can be used for the production of asphalt mixtures with RAP